2023
DOI: 10.1039/d2rp00184e
|View full text |Cite
|
Sign up to set email alerts
|

Generalized rubric for level of explanation sophistication for nucleophiles in organic chemistry reaction mechanisms

Abstract: Reaction mechanisms are central to organic chemistry and organic chemistry education. Assessing understanding of reaction mechanisms can be evaluated holistically, wherein the entire mechanism is considered; however, we assert that such an evaluation does not account for how learners variably understand mechanistic components (e.g., nucleophile, electrophile) or steps (e.g., nucleophilic attack, proton transfer). For example, a learner may have proficiency of proton transfer steps without sufficient proficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(68 citation statements)
references
References 98 publications
(218 reference statements)
7
56
0
Order By: Relevance
“…Several analogous variations of constructed-response items have been reported in the literature for prompting learners to describe what is happening and why for a range of reaction mechanisms Sevian and Talanquer, 2014;Cooper et al, 2016;Caspari et al, 2018a;Crandell et al, 2018Crandell et al, , 2020Dood et al, 2018;Bode ´et al, 2019;Graulich et al, 2019;Deng and Flynn, 2021;Kranz et al, 2023;Yik et al, 2023). While not exclusive to such purposes, these constructed-response items have been presented for use as formative assessments, for promoting learning, and for instructors to respond in real time to the measured learning (Dood et al, 2018(Dood et al, , 2020aYik et al, 2021).…”
Section: Assessing Reaction Mechanisms Learningmentioning
confidence: 98%
See 4 more Smart Citations
“…Several analogous variations of constructed-response items have been reported in the literature for prompting learners to describe what is happening and why for a range of reaction mechanisms Sevian and Talanquer, 2014;Cooper et al, 2016;Caspari et al, 2018a;Crandell et al, 2018Crandell et al, , 2020Dood et al, 2018;Bode ´et al, 2019;Graulich et al, 2019;Deng and Flynn, 2021;Kranz et al, 2023;Yik et al, 2023). While not exclusive to such purposes, these constructed-response items have been presented for use as formative assessments, for promoting learning, and for instructors to respond in real time to the measured learning (Dood et al, 2018(Dood et al, , 2020aYik et al, 2021).…”
Section: Assessing Reaction Mechanisms Learningmentioning
confidence: 98%
“…In developing a rubric to evaluate the level of explanation sophistication for nucleophiles (herein referred to as the nucleophile rubric), Yik et al (2023) reported modifications of a reasoning framework preposed by Dood et al (2020a). The nucleophile rubric includes an Absent level (i.e., a non-normative or no explanation level) not found in the other frameworks reviewed by Dood and Watts (2022a); a possible reasoning for why such a level has been excluded is that prior frameworks tended to be research-focused while the work by Yik et al (2021) focused on developing an assessment tool for instructors and learners to use.…”
Section: Reasoning In Organic Chemistrymentioning
confidence: 99%
See 3 more Smart Citations